Supporting Early-Career Researchers - Elizabeth Kenny (Exchanges: The Interdisciplinary Research Journal, 2024)
This paper explores the pivotal role of recognition in the career progression of emerging researchers in Higher Education. In an ever-competitive academic landscape, early career researchers (ECRs) face numerous challenges, including availability of resources and the struggle to establish themselves. This reflection highlights how ECRs can benefit from support and recognition, both within their academic institutions and the broader scholarly community. It delves into the various forms of recognition, such as awards, grants, publication acknowledgements and promotional progression as well as support mechanisms such as mentorship, training and their impact on researchers’ motivation, professional development, and contributions to their field. Additionally, the paper offers insights into practical strategies and policies that can be employed to better support and empower ECRs on their journey towards academic success. In supporting the ECR community, our future mid-career researchers will be well placed to face future challenges. Recognition, it argues, is not merely a form of validation but a powerful catalyst that fosters innovation, collaboration, and cultivation of a new generation of leaders in research.